Bcl-2 family of proteins as drug targets for cancer chemotherapy: the long way of BH3 mimetics from bench to bedside. (August 2015) - Vela, Laura; Marzo, Isabel
Highlights: Antiapoptotic proteins of the Bcl-2 family are targets for anticancer drugs. BH3 mimetics inhibit antiapoptotic proteins and exert in vitro antitumor activity. Some BH3 mimetics have shown modest activity in clinical trials. More potent and selective BH3 mimetics are under development. Abstract : Bcl-2 proteins are key determinants in the life-death balance. In recent years, proteins in this family have been identified as drug targets in the design of new anti-tumor therapies. Advances in the knowledge of the mechanism of action of anti-apoptotic and pro-apoptotic members of the Bcl-2 family have enabled the development of the so-called 'BH3 mimetics'. These compounds act by inhibiting anti-apoptotic proteins of the family, imitating the function of the BH3-only subset of pro-apoptotic members. Combinations of BH3-mimetics with anti-tumor drugs are being evaluated in both preclinical models and clinical trials. Recent advances in these approaches will be reviewed.